2022
DOI: 10.1002/ehf2.14231
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width as a prognosticator in patients with heart failure

Abstract: Aims Increased red cell distribution width (RDW) is a poor prognostic factor in patients with heart failure (HF). However, only a few large‐scale studies have identified the clinical utility of RDW after adjusting for covariates affecting RDW. Methods and results From January 2010 to April 2021, we retrospectively enrolled patients diagnosed with HF from three referral hospitals with available RDW data (taken within 3 months of HF diagnosis) using an integrated clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Several studies showed that the RDW in combination with NT‐proBNP improved the prognostic value in a traditional model in patients with acute or chronic HF 12,15,45 . In addition, many studies have shown that the baseline RDW is an independent predictive marker for all‐cause mortality in patients with acute or chronic HF 8,13,14,46 . Moreover, a high RDW was also associated with increased all‐cause mortality, even in patients with advanced HF who underwent cardiac resynchronization therapy, 47,48 implantation of a left ventricular assist device, 49,50 or heart transplantation 51 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies showed that the RDW in combination with NT‐proBNP improved the prognostic value in a traditional model in patients with acute or chronic HF 12,15,45 . In addition, many studies have shown that the baseline RDW is an independent predictive marker for all‐cause mortality in patients with acute or chronic HF 8,13,14,46 . Moreover, a high RDW was also associated with increased all‐cause mortality, even in patients with advanced HF who underwent cardiac resynchronization therapy, 47,48 implantation of a left ventricular assist device, 49,50 or heart transplantation 51 .…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 15 , 45 In addition, many studies have shown that the baseline RDW is an independent predictive marker for all‐cause mortality in patients with acute or chronic HF. 8 , 13 , 14 , 46 Moreover, a high RDW was also associated with increased all‐cause mortality, even in patients with advanced HF who underwent cardiac resynchronization therapy, 47 , 48 implantation of a left ventricular assist device, 49 , 50 or heart transplantation. 51 In our study, the ΔRDW improved the risk stratification for short‐ and long‐term mortality in the established model including baseline RDW and NT‐proBNP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher the RDW value, the greater the change in red blood cell size. Fluctuations in RDW have been reported in many pathophysiological conditions; for example, elevated RDW is associated with acute and chronic heart failure [ 9 ], coronary artery disease, cerebral infarction, and acute myocardial infarction [ 10 ]. Previous studies have reported an association between elevated RDW levels in elderly patients and unfavorable outcomes in terms of overall survival (OS) and disease-free survival (DFS) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%